Eksplorasi Mikroba Penghasil Enzim-enzim Hidrolitik Di Kawasan Taman Nasional Lore Lindu Sulawesi Tengah - Rahmiati, Rahmiati; Pujianto, Sri; Kusdiyantini, Endang (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2016)
Lore Lindu National Park (TNLL) is an area that flora, fauna and microbes, the diversity of microbes producing hydrolytic enzyme. explore the hydrolytic enzyme producing microbes in Indonesia. This study was aimed to obtain bacterial isolates were able to produce hydrolytic enzyme and characteristics. Isolation in the microbiology laboratory. Isolation by a spread plate. Isolates in the selection hydrolytic enzyme producing selective media. Measurement of the activity of the enzyme with hydrolytic index. The results were thirteen isolates clearing zone test , 2 protease enzyme bacterial isolates, 1 lipase enzyme bacterial isolates, 6 amylase enzyme bacterial isolates, while 4 cellulase enzyme bacterial isolates. Examination of Amylase enzyme activity was done using DNS method. L10T3 showed that the bacterial isolate optimum activity at pH 7 and at a temperature of 300C with an activity of 0.040 U / mL and 0.029 U / mL. Key word: Lore Lindu National Park, hydrolytic enzyme. isolation of bacteria